The ultimate guide to hiking : more than 100 essential skills on campsites, gear, wildlife, map reading, and more - McDougall, Len (Skyhorse Publishing, 2021)
Readers interested in the outdoors will find out how to choose the best gear, how to set up a campsite, how to interact safely with wildlife, how to read a map, how to forecast the weather, along with learning practical navigation skills.